Perancangan Komunikasi Visual Oleh-Oleh Khas Surabaya “Guna Guna Snack” Berbasis Pop Art Sebagai Upaya Meningkatkan Brand Awareness - YULIVIANA, LISA ACDHA; Budiardjo, Hardman; Yurisma, Dhika Yuan (Jurnal Art Nouveau, 2017)
Guna Guna Snack is one of the local food producers in Surabaya. Guna Guna Snack become signature’s of Surabaya since early 2012. The problem is, at this time there are many competitors offer the same products as Guna Guna Snack. So, to attract attention and introduce products to consumers requires their visual communication design such as media promotion to communicate a message for introduce product of Guna Guna Snack and to differentiate Guna Guna Snack with the other signature’s of Surabaya. The research methodology that is used a qualitative methodology with data collection through observation, interviews, documentation, literature, existing studies, and competitors studies. The result of these research will be made a visual communication design such as media promotion in three categories: Above The Line (ATL), Below The Line (BTL), and Through The Line (TTL). With youthful concept and visual displays based on pop art, hopefully it can be representing the face of Guna Guna Snack. The pop art visual later will be used as a tool for media promotion to deliver the message well so that people will recognize Guna Guna Snack. Keywords: Design, Visual Communication, Signature’s of Surabaya, Guna Guna Snack, Pop Art,Youthful, Brand Awareness